Praktik Akad Mudharabah Kontemporer Pada Perbankan Syariah Indonesia - Kartika; Sabbar Dahham Sabbar (CBJIS: Cross-Border Journal of Islamic Studies, 2024)
The modern economic era requires Islamic banking to create financial products that are competitive, transparent, and in accordance with sharia principles, including the implementation of mudharabah contracts. The transformation of mudharabah contracts from classical to contemporary forms reflects the efforts of Islamic banking to meet market demands while maintaining sharia values. This study aims to identify the characteristics of mudharabah contract transformation in Indonesian Islamic banking, analyze the obstacles faced, and explore strategies that can be implemented to improve its effectiveness. The research method uses a descriptive qualitative approach with a literature study through document analysis and secondary data related to mudharabah practices in Indonesia. The results show that the transformation of the mudharabah contract includes technical adjustments such as the application of revenue sharing, the introduction of collateral, and limiting the freedom of mudharib through mudharabah muqayyadah. However, the implementation of this contract still faces challenges in the form of moral hazard risk, non-uniform regulations, and public resistance to the principle of profit sharing. Theoretically, this research contributes to the literature of Islamic economics, especially in the development of an adaptive Islamic contract model that is consistent with maqashid sharia. Practically, this study offers guidance for Islamic banks in designing mudharabah-based products, education for the public to improve their understanding of the principle of profit sharing, and recommendations for regulators in strengthening regulations. This study concludes that the success of mudharabah contracts requires strengthening regulations, product innovation, and more intensive public education, so as to increase the competitiveness of Islamic banking in Indonesia.